COMPARATIVE EVALUATION OF DIFFERENT ECBOLIC THERAPIES ON PUERPERIUM IN DYSTOCIA AFFECTED DANGI COWS - BHOI, D B; KHASATIYA, C T; DESAI, V K (The Indian Journal of Animal Reproduction, 2020)
The study was conducted to evaluate the effect of different ecbolic therapies on puerperium in eighteen dystocia affected Dangi cows divided into three groups consisting of six cows in each. Group-I (T1) and II (T2) cows were injected methylergometrine (5 mg) and dinoprost tromethamine (25 mg) i/m, respectively, immediately after parturition. The cows in Group-III (T3) received herbal ecbolic, 2-4 boluses, bid for first10 days postpartum. The time required for placental expulsion and uterine involution in T1 (3.41±0.30 hrs; 28.00±0.57 days) were non-significantly (P>0.05) higher than T2 (2.00±0.44 hrs; 24.66±0.76 days) and the values for both T1 and T2 were significantly (P<0.05) higher in T3 (5.75±0.80 hrs; 33.00±1.77 days) group. The number of services per conception did not differ significantly (P>0.05) between T1 (1.66±0.33), T2 (2.00±0.25) and T3 (2.50±0.22). The conception rate was found 50 % in T1 and 100 % in T2 and T3 with an overall conception rate of 83.33 % for all three treatment groups of Dangi cows.